The structure and function of the land and tree tenure systems and Agroforestry in the Brong Ahafo Region of Ghana - Amoh, Christiana Pomaa (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of Master of Science Degree in Agroforestry,